Single molecule localization microscopy analyses of DNA-repair foci and clusters detected along particle damage tracks - Hausmann, Michael; Neitzel, Charlotte; Heermann, Dieter W.; Hildenbrand, Georg Lars (Frontiers in physics, 2020)
High-LET particle irradiation as being provided from heavy ion accelerator facilities has an increasing impact on bio-medical research and cancer treatment. Nevertheless, there are a lot of open questions concerning the understanding of damaging mechanisms and repair processes within the light of radio-sensitivity and thus, individualized medical applications. The three-dimensional architecture of genomes on the meso- and nano-scale acts in combination with epigenetic gene activation as an important player of gene regulation and fundamental biological processes such as DNA damage response and repair. So far only little is known about the impact of high-LET particles on the chromatin architecture along the passing track when they are “lumbering” through the cell nucleus. How does a cell nucleus manage such complex damages and re-organize the chromatin towards functionally intact units? Is there a radio-sensitivity related difference in this reaction? Here, we present some approaches to investigate spatial and topological parameters of chromatin to glimpse some aspects related to these questions. Two cell lines, a radio-resistant glioblastoma and a radio-sensitive fibroblast cell line, were used and irradiated by N-ions in 90° and 10° radiation beam geometry. Nano-probing of particle induced damage sites along particle tracks, and the recruited DNA repair proteins (as presented here for 53BP1and Rad51) in combination with super-resolution Single Molecule Localization Microscopy (SMLM) are powerful methods for geometric and topological analyses to study particle related mechanisms of chromatin conformation and repair complexes in single cells. We used variable tools for such investigations based on image free high precision SMLM, nano-scaled molecule distribution analyses, appropriate metrics following Ripley´s distance frequencies and cluster formation analyses, as well as topological quantifications employing persistence homology. The data reveal a cell type specific nano-architecture of DNA damage foci along particle tracks and their dynamic molecular re-arrangements during repair. Comparing the topology of repair foci by persistence homology suggests similarities of repair cluster formation along given particle tracks. Our studies contribute to the molecular understanding of cellular radiation response at sub-light microscopic chromatin levels; thereby showing how chromatin architecture around complex damage sites and repair foci nano-architecture may contribute to ongoing repair processing.
Gesehen am 19.11.2020